Competitiveness of Small and Medium Firms (SMEs) in Facing ASEAN Economic Community - Ricky Rengkung, Leonardus; Pangemanan, Lyndon Reinhardt J.; Sondak, Lorraine W. (Universitas Prasetiya Mulya, 2017)
The purpose of this study is to develop a model of Resource-based View (RBV) and to analyze the competitiveness of Manado Small and Medium firms (SMEs) in facing the ASEAN Economic Community (AEC), based on valuable, rare, inimitable, and non-substitutable (VRIN) resources of Resource-based View (RBV). To answer these purposes, the proportional stratified random sampling was conducted by taking 180 small and medium firms (SMEs) in Manado, consist of 90 small firms and 90 medium firms. The data were analyzed using qualitative systems dynamics analysis. The results indicated that holistically, systemic behavior of VRIN resources makes a contribution on Manado SMEs' competitiveness in facing the implementation of ASEAN Economic Community (AEC), both before and after intervention. Before intervention, decline of VRIN resources makes contribution on decline of the competitiveness of Manado SMEs. On the contrary, after intervention, increase of VRIN resources makes contribution on increase of the competitiveness of Manado SMEs. Partially, rare (R) resources make more contribution than non-substitutable (N), imperfectly imitable (I), and valuable (V) resources on competitiveness. It can be concluded that these systemic behaviors of VRIN resources make contribution both negatively in declining and positively on increasing competitiveness of Manado SMEs.